The Mediating Role of Cognitive Emotion Regulation, Cognitive Biases, and Negative Schemas in the Relationship between Traumatic Childhood Experiences and Psychotic-Like Experiences - Dorna nabizadeh asl; qasem ahi; Fatemeh Shahabizadeh; Ahmad Mansouri4 (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2020)
Aim and Background: Psychotic-like experiences are considered non-clinical and mild forms of psychotic disorders that are associated with negative consequences such as distress, mental disorders and functional impairments. In addition, they can lead to clinical psychosis. Therefore, the present study aimed to investigate the mediating role of cognitive emotion regulation, cognitive biases, and negative schemas in the relationship between traumatic childhood experiences and psychotic-like experiences. Methods and Materials: The research was descriptive-correlational. The statistical population consisted of all students of Islamic Azad University, Birjand branch (N=5700) in the academic year of 2019-2020. The sample size was 400 people who were selected by cluster random sampling. In order to collect data, Childhood Trauma Questionnaire (CTQ), Cognitive Emotion Regulation Questionnaire (CERQ), Davos Assessment of Cognitive Biases Scale (DACOBS), Brief Core Schema Scales (BCSS) and the 16-item version of the Prodromal Questionnaire (PQ-16) were used. The present research data were analyzed using SPSS and LISREL software and structural equation modeling. Findings: The results showed that traumatic childhood experiences have a significant effect on the cognitive emotion regulation, cognitive biases and negative schemas (p <0.05). Cognitive emotion regulation, cognitive biases, and negative schemas have a significant effect on the psychotic-like experiences (p <0.05). Also, cognitive emotion regulation, cognitive biases, and negative schemas mediated the relationship between traumatic childhood experiences and psychotic-like experiences. Conclusions: The results of the present study support the hypothesis that cognitive emotion regulation, cognitive biases, and negative schemas mediate the relationship between traumatic childhood experiences psychotic-like experiences.